2011
DOI: 10.1093/cid/ciq195
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemia among HIV-infected Patients with Tuberculosis Taking Once-daily Nonnucleoside Reverse-Transcriptase Inhibitor-Based Antiretroviral Therapy in India

Abstract: HIV-infected patients with tuberculosis who initiate nonnucleoside reverse-transcriptase-based anti-retroviral treatment in combination with rifampicin-based antituberculosis treatment demonstrate increases in total cholesterol, low-density cholesterol, and high-density cholesterol levels but no change in blood glucose level after 1 year. Cholesterol increases were more frequent among patients receiving efavirenz.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
35
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 12 publications
5
35
2
Order By: Relevance
“…This is comparable with the prevalence reported from Hawasa-Ethiopia which is 43.4% [29]. However, the prevalence of HDL-c < 40mg/dl among on HAART HIV positive persons is higher than the prevalence reported from Jimma-Ethiopia (32.6%) [30]. The prevalence of LDL-c ≥ 150mg/dl in our HAART group was 48.3%.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This is comparable with the prevalence reported from Hawasa-Ethiopia which is 43.4% [29]. However, the prevalence of HDL-c < 40mg/dl among on HAART HIV positive persons is higher than the prevalence reported from Jimma-Ethiopia (32.6%) [30]. The prevalence of LDL-c ≥ 150mg/dl in our HAART group was 48.3%.…”
Section: Discussionsupporting
confidence: 83%
“…The prevalence of raised TG on HAART group was 59.6%, which is comparable with the report from Hawasa-Ethiopia (55.8%) [29]. But our finding was higher than studies done in; India, Cameron, Jimma-Ethiopia [24,30,31] reported 32%, 39%, 18.2%, respectively. However, there are suggestions that the magnitude of lipid profile derangements induced by HAART showed variation with duration of treatment, across populations and setting.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Derangements of lipid metabolism associated with HAART have been described particularly in patients on treatment regimens including PIs and d-4T [23], but also for treatment regimens including NVP and EFV [24,25]. Our study did not assess the global cardiovascular risk of participants.…”
Section: Discussionmentioning
confidence: 95%
“…Evidences in support of lipodystrophy and dyslipidaemia associated with First-line HAART in our area are scarce [10,11]. The aim of the present study was 1) to study and compare Lipid profile in HIV positive patients on ART with that of freshly diagnosed HIV positive patients who were yet to be started on ART.…”
Section: Discussionmentioning
confidence: 99%